Atypical Presentation of Cat-Scratch Disease in an Immunocompetent Child with Serological and Pathological Evidence. (25th December 2014) - Atıcı, Serkan; Kadayıfcı, Eda Kepenekli; Karaaslan, Ayşe; Toper, Muhammed Hasan; Celikel, Cigdem Ataizi; Soysal, Ahmet; Bakır, Mustafa
Abstract : Typical cat-scratch disease (CSD) is characterized by local lymphadenopathy following the scratch or bite from a cat or kitten. An atypical presentation which includes liver and/or spleen lesions is rarely reported in an immunocompetent child. Systemic CSD may mimic more serious disorders like malignancy or tuberculosis. Although a diagnosis is difficult to establish in systemic CSD, an early diagnosis and an appropriate treatment are important to prevent complications. Bartonella henselae is difficult to culture, and culture is not routinely recommended. Clinical, serological, radiological, and pathological findings are used for the diagnosis of CSD. Herein we present a case of systemic CSD presenting with hepatic mass in an immunocompetent child. The differential diagnosis is made by serological and pathological evidence. He was successfully treated with gentamicin (7.5 mg/kg) and rifampin (15 mg/kg) for six weeks.